Concussion knowledge, attitudes and reporting intention among adult competitive Muay Thai kickboxing athletes: a cross-sectional study - Reidar P. Lystad (Injury Epidemiology, 2018)
Abstract Background Muay Thai kickboxing is a full-contact combat sport with a high incidence of head trauma, yet little is known about these athletes’ concussion knowledge and attitudes. This study aims to describe and quantify concussion knowledge, attitudes, and reporting intention among adult competitive Muay Thai kickboxing athletes. Results This cross-sectional study comprised 193 competitive Muay Thai kickboxing athletes aged ≥18 years registered with the Thai Boxing Association Sanctioning Authority. The mean concussion knowledge score was 19.5 (SD 2.3) out of 25, the mean concussion attitudes score was 62.7 (SD 7.4) out of 75, and 134 (69.4%) of respondents indicated that they were likely to report concussion symptoms. No significant predictors of concussion knowledge, attitudes, or reporting intention were revealed. Conclusions Competitive Muay Thai kickboxing athletes appear to have reasonably good concussion knowledge, attitudes, and reporting intention; however, there is still room for further improvement. It is recommended that concussion education programs based on current best evidence are made available to all kickboxing athletes and coaches.